Evaluation of blood reservation and use for caesarean sections in a tertiary maternity unit in south western Nigeria - Oshodi Yussuf A; Rabiu Kabiru A; Tayo Adetokunbo O; Fabamwo Adetokunbo O; Akinola Oluwarotimi I; Onyekwere Chioma A (BMC, 2010)
Abstract Background Haemorrhage from obstetric causes is the most common cause of maternal mortality in the developing world. Prevention of mortality from haemorrhage will necessarily involve prompt blood transfusions among other life saving measures. There are however limited stocks of fresh or stored blood in many health care facilities in Sub Saharan Africa. Caesarean section has been identified as a common indication for blood transfusion in obstetrics practice and its performance is often delayed by non availability of blood in our centre. An evaluation of blood reservation and use at caesarean sections in a tertiary maternity unit in Lagos, south western Nigeria should therefore assist in formulating the most rational blood transfusion policies. Methods Case records of 327 patients who had elective and emergency caesarian sections at the Lagos State University Teaching Hospital between 1st October and 31st December 2007 were reviewed. Data pertaining to age, parity, booking status, type and indication for Caesarean section, pre- and post-operative packed cell volume, blood loss at surgery, units of blood reserved in the blood bank, unit(s) of blood transfused and duration of hospital stay was extracted and the data analysed. Results There were 1056 deliveries out of which 327 (31%) were by Caesarean section. During the study period, a total of 654 units of blood were reserved in the blood bank and subsequently made available in theatre. Out of this number, only 89 (13.6%) were transfused to 41 patients. Amongst those transfused, twenty-six (54%) were booked and 31 (75.6%) had primary caesarian section. About 81% of those transfused had emergency caesarean section. The most common indication for surgery among those transfused were placenta praevia (9 patients with 21 units of blood) and cephalo-pelvic disproportion (8 patients with 13 units). Conclusion Even though a large number of units of blood was reserved and made available in the theatre at the time of operation, majority of the patients operated did not need blood transfusion. Provision of a mini- blood bank within the obstetric unit and careful patient categorization will ensure timely availability of blood for surgery without necessarily tying down stock in the central blood bank.